Blending issues and stakeholders: in pursuit of the elusive synergy. Issue 3 (7th November 2016) - Mahon, John F.; Heugens, Pursey P.M.A.R.; McGowan, Richard A.
Abstract: Two separate frameworks have existed for the analysis of social predicaments in which businesses play a role: issues management and stakeholder management. In this paper, we argue that the chasm dividing these two literatures is artificial, and potentially obstructive to the advancement of our knowledge of the position of business in contemporary societies. The position we take in the present paper is that all social predicaments have an issues side as well as a stakeholder side and that a dual focus on both issues and stakeholders is therefore essential to understanding the evolution of these predicaments and crucial to managerial dealings with these issues. We present an integrative co‐evolutionary framework, explaining the dynamics between issues and stakeholders in all consecutive stages of a predicament's evolution. The framework proposes a new way of thinking about issues and stakeholders, as such facilitates a deeper understanding of how the social environment of business is constituted, and offers new insights for the practical management of issues and stakeholders.